2009
DOI: 10.1137/080712593
|View full text |Cite
|
Sign up to set email alerts
|

A New Total Variation Method for Multiplicative Noise Removal

Abstract: Image denoising plays a important role in the areas of image processing. A real recorded image may be distorted by many expected or unexpected random factors, of which random noise is a unavoidable one.Multiplicative noise is naturally dependent on the image data, the recorded image g is the multiplication of original image u and noise n: g = un.(1)Here u, g and n are n 2 -by-1 vector corresponding to n-by-n image. whereis the data fitting term, u T V is the total variation (TV) regularization term [1], λ is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
244
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(252 citation statements)
references
References 13 publications
0
244
0
Order By: Relevance
“…They applied a corresponding relaxed inverse scale space flow as denoising technique. The model of Shi and Osher was modified in [42] by adding a quadratic term to get a simpler alternating minimization algorithm. A variational model involving curvelet coefficients for cleaning multiplicative Gamma noise was considered in [24].…”
Section: Introductionmentioning
confidence: 99%
“…They applied a corresponding relaxed inverse scale space flow as denoising technique. The model of Shi and Osher was modified in [42] by adding a quadratic term to get a simpler alternating minimization algorithm. A variational model involving curvelet coefficients for cleaning multiplicative Gamma noise was considered in [24].…”
Section: Introductionmentioning
confidence: 99%
“…The symmetric alternating direction method with multipliers (symmetric ADMM) is an acceleration method of ADMM, which can be used to solve the constraint optimization formulation in image processing [34][35][36][37][38][39][40][41][42][43].…”
Section: Symmetric Admmmentioning
confidence: 99%
“…Although the domain B is nonnegative in real applications, through the dual formulation of the Bregman-divergence (17), the nonpositive domain is very common and sometimes is useful for convex reformulation of nonconvex variational models appearing in SAR image enhancement problems. See Theorem 7 for the negative domain of the conjugate function Φ * .…”
Section: Bregman Variational Model-bregman-tvmentioning
confidence: 99%
“…Actually, this model is highly nonconvex [15]. Therefore, various transforms are introduced to relax nonconvexity of the Gamma distribution related speckle reduction model [16][17][18][19][20][21]. Recently, we have shown that the β-divergence with β ∈ (0, 1) can be used as a transform-less convex relaxation model for SAR speckle reduction problem [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation